HUMORAL AND PROTECTIVE RESPONSE OF INDIAN MAJOR CARPS TO IMMERSION VACCINATION WITH AEROMONAS HYDROPHILA - Kalita, B.; Mohan, C. V.; Shankar, K. M.; Azad, I. S. (Journal of Indian Fisheries Association, 2006)
Fry of the Indian major carps, Cat/a cat/a (Ham.), Labeo rohita (Ham.)and Cirrhinus mrigala (Ham.) were immunized at 4 and 8 weeks post hatching (wph) by direct immersion in a suspension (1 08 cells mr1) of heat inactivated Aeronwnas hydrophila. Following the same procedure, booster dose was administered 20 days after the first immersion. Antibodies as well as protective response produced in both the groups after the first and the booster immersion were different and significant (P